Legal Nature and Regulatory Models of Zero-Hours Contracts in a Comparative Legal Perspective - Irakli Shamatava; Mariam Ivanidze; Nino Gulbatashvili (European Scientific Journal, ESJ, 2026)
A zero-hours contract represents a form of non-standard employment under which the employer does not undertake an obligation to provide the employee with a minimum number of workings hours, while the performance of work depends on the employer's current operational needs and fluctuations in labor demand. In modern doctrine, it is not regarded as a unified and clearly defined legal category, which renders the issue of its labor-law qualification particularly topical. Zero-hours contracts are widely prevalent in numerous European jurisdictions, however, Georgian labor legislation does not provide for their specific regulation. This regulatory gap gives rise to significant theoretical and practical challenges in terms of their labor-law qualification and the effective protection of the employee as the weaker party to the employment relationship.The purpose of this study is to determine the labor-law qualification of the zero-hours contract and to distinguish it from a Service Agreement (service contract). The research is based on doctrinal, comparative-legal, and functional methods. It analyzes the legal models of the United Kingdom, Ireland, Germany, and the Netherlands, alongside international labor standards and contemporary doctrinal approaches.The results of the study demonstrate that the zero-hours contract does not constitute an independent labor-law institution. Its legal qualification shall be executed based on the actual content of the relationship, while in the presence of characteristics inherent to an employment relationship, such a relationship shall be assessed as an employment relationship, regardless of the formal title of the contract. In this regard, the criteria of subordination, personal performance, organizational integration, and economic dependence are of decisive importance.The current legal framework of Georgia allows for the assessment of relationships arising within the scope of a zero-hours contract based on the general criteria of an employment relationship; however, the absence of specific regulation creates a risk of legal uncertainty in practice.